Leveraging artificial intelligence applications to develop English language skills and foster sustainable development awareness among Saudi university students: A step towards future economies - Lamouchi, Ali; Sadek Elsayed, Mustafa; Abdellatif, Mohamed; Aly , Shaban (Research Journal in Advanced Humanities, 2025)
This research aims to examine the effectiveness of utilizing artificial intelligence (AI) applications in enhancing Saudi undergraduate students’ English language skills while simultaneously promoting their attitudes toward sustainable development, aligning with the Kingdom’s vision for building future-ready economies. A total of 23 first-year students from the Applied College at Prince Sattam bin Abdulaziz University participated in the study, with 12 students assigned to the experimental group and 11 to the control group. The study employed an AI-based training program, an English language proficiency test, and an attitude scale toward sustainable development. Using a quasi-experimental design and statistical analyses, including Mann-Whitney and Wilcoxon tests, the findings revealed statistically significant differences favoring the experimental group in both English language skills and attitudes toward sustainability. Moreover, the results confirmed that the positive effects of the AI-based training persisted in follow-up measures, indicating sustainable impact. By demonstrating the role of AI tools in strengthening students’ communication skills and sustainable mindset, this study highlights the importance of integrating advanced technologies in higher education to prepare human capital for knowledge-based economies. Recommendations and directions for future research are presented to further support the strategic national priority of transitioning toward diversified, innovation-driven economic growth.